Female Speakers Benefit More Than Male Speakers From Prosodic Charisma Training—A Before-After Analysis of 12-Weeks and 4-h Courses - Niebuhr, Oliver; Tegtmeier, Silke; Schweisfurth, Tim (Frontiers in Communication, 2019)
Empirical studies not just show that perceived charisma is an important success factor in professional life; they also show that female speakers need to overcome higher intrinsic and extrinsic hurdles than male speakers in order to create the same charismatic effect. Prosody is probably the most influential instrument for speaker charisma. We have developed a system called "Pascal" that analyzes and assesses on objective acoustic grounds the use of seven prosodic parameters in business presentations. It is used for charismatic-speech training in 12-week and 4-hour courses on entrepreneurship and leadership. Comparing the Pascal scores for a total of 72 participants at the beginning and end of these two course types showed that female speakers start with significantly lower prosodic-charisma scores, but then learn so much faster and more than male speakers that they are able to catch up with male speakers in 4-hour courses and significantly reduce the gap to male speakers in 12-week courses. Given that leadership and entrepreneurship are still male-dominated domains, our results can be seen as an encouragement for women to attend prosodic charisma trainings.